2002
DOI: 10.1002/jbt.10037
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of thrombine‐signaling mechanism by heptachlor in human platelets

Abstract: Heptachlor is a persistent organochlorine insecticide that has been detected in human tissues and fluids. The ability of heptachlor to interfere with platelet phosphoinositides metabolism and related signaling events stimulated by thrombin was evaluated. In vitro incubations with a concentration range of 1-100 microM heptachlor, prior to platelets activation, were performed. Experiments showed that 10 microM increased protein Kinase C (PKC) activity and phosphatidylinositolbiphosphate and phosphatidic acid pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…Since phosphoinositides are important components of the hormone signaling pathway in different tissues [11][12][13] and previous reports from our laboratory describe the alteration in their metabolic pathways produced by several pesticides [14][15][16], we focused our attention in this paper on the study of placenta phosphoinositides metabolism as a potential target of pesticides action. We also examined the effect of OC and OP pesticides on the activity of PI 4-kinase [17] a key enzyme in this metabolic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Since phosphoinositides are important components of the hormone signaling pathway in different tissues [11][12][13] and previous reports from our laboratory describe the alteration in their metabolic pathways produced by several pesticides [14][15][16], we focused our attention in this paper on the study of placenta phosphoinositides metabolism as a potential target of pesticides action. We also examined the effect of OC and OP pesticides on the activity of PI 4-kinase [17] a key enzyme in this metabolic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…al., 2005). Investigaciones del Libiquinia (Laboratorio de biologia, quimica y ambientc) de la Universidad Nacional del Comahuc, vicncn mostrando consecuencias carcinogénicas y otros cfcctos perjudiciales de los venenos que se usan para controlar plagas de los monocultivos en ci Alto Valle de Rio Negro y Neuquén (Magnarelli et. al.…”
Section: Introductionunclassified
“…Moya de Juri et al [40] evaluated the ability of the OC heptachlor (HC) to interfere with platelet phosphoinositides metabolism and related signaling events stimulated by thrombin. They found that HC 1 and 10 μM increased PKC activity and PtdIns-4,5-P2 and PA phosphorylation but 100 μM HC increased PtdIns-4,5-P2 phosphorylation and reduced serine/threonine kinases activity.…”
Section: Organochlorine Pesticides Effectsmentioning
confidence: 99%